Enhanced performance of sediment microbial fuel cell by immobilization of Shewanella oneidensis MR-1 on an anode surface. (19th April 2019) - Shi, Juanjuan; Zhao, Shuai; Yu, Xuan; Zhou, Tuoyu; Khan, Aman; Yu, Zhengsheng; Feng, Pengya; Wang, Jicun; Liu, Pu; Li, Xiangkai
Abstract: The anodic microbial community especially relative abundance of exoelectrogens is crucial for performance enhancement of sediment microbial fuel cell (SMFC). In this study, Shewanella oneidensis MR-1 was immobilized on an active carbon fiber anode and the SMFC's performance was evaluated. The maximum power density of SMFC with immobilized strain MR-1 (SMFC-ImSW) displayed 61.0 mW/m 2, and SMFC with conventional bioaugmentation (SMFC-SW) and no treatment (SMFC-CK) of strain MR-1 obtained 11.1 and 2.4 mW/m 2, respectively. The chemical oxygen demand removal efficiency of SMFC-ImSW was 14.2% and 24.2% higher than SMFC-SW and SMFC-CK groups, respectively. Furthermore, the organics removal efficiencies of sediment were also increased in SMFC-Imsw. GFP-tagging and RT-PCR results showed that strain MR-1 was colonized on the anode biofilm of SMFC-ImSW. Cyclic voltammetry and Electrochemical impedance spectroscopy results showed that higher redox potential and charge transfer efficiency presented with immobilized strain MR-1. MiSeq sequencing results showed that Sphaerochaetaceae and Marinilabiaceae were also enriched on the anode biofilm, which are related to power generation. These results demonstrated that immobilized bioaugmentation is an ideal approach to improve SMFC performance. Highlights: SMFC with immobilization was applied for improving system performance. The power output significantly increased in the SMFC with immobilization. Immobilization can promote abundance of the genus Shewanella in anode biofilms. Bacteria related to electricity generation were enriched at the anode biofilm.